STRUGGLE FOR NORMAL LIFE IN DAVID FINCHER'S THE CURIOUS CASEOF BENJAMIN BUTTON : AN INDIVIDUAL PSYCHOLOGICAL APPROACH - PERKASA, DIKHY INDRA (2011)
The major problem of this study is to elucidate the struggle for a better life of Benjamin Button reflected in David Fincher's The Curious Case of Benjamin Button. The objectives of the study are; to analyse the structural elements of the movie and to analyse the character of Benjamin Button based on individual psychological perspective. In conducting this study, the researcher uses qualitative research in which the data are based on primary data the movie David Fincher's The Curious Case of Benjamin Button itself. While secondary data are David Fincher's biography and other data which deal with the research. In analyzing the data, he applies two approaches. Firstly, structural approach is used to analyze the elements of the movie. Firstly, the writer analyzes the narrative elements of the movie. Consisting of characters and characterization, setting, plot and point of view and theme. Secondly, the writer discussed the technical elements of the movie. Covering mise-en-scene, cinematography, sound and editing. Then, the individual psychological approach is used for analyzing the struggle for better life and optimism of Benjamin Button that influences his daily activity and behavior toward life. These approaches are applied in order to get the appropriate analysis and answer the problems. The writer finds that Benjamin Button's struggle for a better life leads him to an autonomous personality that has a great self confident in life.